Diagnostic performance of dynamic 3D magnetic resonance angiography in daily practice for the detection of intracranial arteriovenous shunts in patients with non-traumatic intracranial hemorrhage - Roumi, Arnaud; Ben Hassen, Wagih; Hmeydia, Ghazi; Posener, Sacha; Pallud, Johan; Sharshar, Tarek; Calvet, David; Mas, Jean-Louis; Baron, Jean-Claude; Oppenheim, Catherine; Naggara, Olivier; Turc, Guillaume (Frontiers in Neurology, 2023)
Introduction Identification of treatable causes of intracranial hemorrhage (ICH) such as intracranial arteriovenous shunt is crucial to prevent recurrence. However, diagnostic approaches vary considerably across centers, partly because of limited knowledge of the diagnostic performance of first-line vascular imaging techniques. We assessed the diagnostic performance of dynamic three-dimensional magnetic resonance angiography (dynamic 3D MRA) in daily practice to detect intracranial arteriovenous shunts in ICH patients against subsequent digital subtraction angiography (DSA) as reference standard. Methods We reviewed all adult patients who underwent first-line dynamic 3D MRA and subsequent DSA for non-traumatic ICH between January 2016 and September 2021 in a tertiary center. Sensitivity, specificity, accuracy, positive and negative predictive values of dynamic 3D MRA for the detection of intracranial arteriovenous shunt were calculated with DSA as reference standard. Results Among 104 included patients, 29 (27.9%) had a DSA-confirmed arteriovenous shunt [19 pial arteriovenous malformations, 10 dural arteriovenous fistulae; median onset-to-DSA: 17 (IQR: 3–88) days]. The sensitivity and specificity of dynamic 3D MRA [median onset-to-dynamic 3D MRA: 14 (3–101) h] for the detection of intracranial arteriovenous shunt were 66% (95% CI: 48–83) and 91% (95% CI: 84–97), respectively. The corresponding accuracy, positive and negative predictive values were 84% (95% CI: 77–91), 73% (95% CI: 56–90), and 87% (95% CI: 80–95), respectively. Conclusion This study suggests that although first-line evaluation with dynamic 3D MRA may be helpful for the detection of intracranial arteriovenous shunts in patients with ICH, additional vascular imaging work-up should not be withheld if dynamic 3D MRA is negative. Comparative prospective studies are needed to determine the best imaging strategy to diagnose arteriovenous shunts after non-traumatic ICH.